Estratégias de comercialização adotadas por famílias que praticam agrofloresta: um estudo de caso no assentamento Mário Lago, Ribeirão Preto/SP - Nunes, Patricia Joia (2017)
Throughout its history, the Landless Rural Workers Movement (MST) has builtdifferent ways of making life possible in its rural settlements in order to generate income, stay in the countryside and care for nature, for both issues and organization Of the territory, production and commercialization gained body through the proposals of agricultural cooperation and agroecology. From this context, since the end of 2011, the Mário Lago settlement, located in Ribeirão Preto / SP, has leveraged agroforestry and commercialization, becoming an important reference for the experiences of other rural settlements in the country. Therefore, the general objective of this work was to identify and analyze commercialization strategies adopted by the families involved and to reflect on the economic, social and political implications that involve the life of the subjects of this process, highlighting potential and difficulties, the specific objectives were to identify the possibilities To the country's rural settlements; Describe the strategies used by the farmers of the "Mário Lago" settlement; To carry out a survey of primary data, which were addressed to issues such as: products traded in agroforestry containing variety and quantities; Of the average incomeper farmer within the marketing strategy adopted, among others. The research was exploratory with analysis of secondary data and primary data collection with 25 families interviewed. From the data, the SWOT analysis was applied (FOFA) and it was concluded that the experience of the commercialization via agroforestry baskets represented an important increase in the income of the producers that market it and provided autonomy to the farming families; Thus, this form of commercialization becomes an important reference for other possible experiences in settlements in the state of São Paulo.A